Perlindungan Hukum Kekayaan Intelektual Terhadap Pengrajin Kerajinan Marmer Di Tulungagung - Tikka Dessy Harsanti; Vivi Sylvia Purborini; Roy Anugrah; Neiska Kurnia Dewi; Muhammad Afandi Azharuddin (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The importance of understanding intellectual property legal protection for marble craft craftsmen in Tulungagung. As an area famous for marble crafts, Tulungagung has many craftsmen whose intellectual property rights need to be protected. This protection is deemed necessary considering the rapid development of the marble craft industry in Tulungagung. focuses on in-depth understanding of the protection of marble craftsmen's intellectual property rights. This approach allows researchers to gain rich and detailed insights into intellectual property rights protection practices in the context of the marble artisan industry. Marble craftsmen in Tulungagung still need stronger intellectual property legal protection to prevent cases of copyright and trademark infringement. The government and related institutions need to increase outreach and education to marble craftsmen regarding the importance of legal protection of intellectual property, as well as simplify the registration process for copyrights, trademarks and industrial designs so that craftsmen can easily protect their work legally. Marble crafts in Tulungagung have high artistic and economic value.